Comparison Of Carbon Footprints Between Internal Combustion Engine, Hybrid And Electric Vehicles Selected Case Study - Adzman, Muhammad Syazwan Kamarul (Universiti Sains Malaysia, 2021)
The global warming is a very concerning issue right now especially when the use of transportation is increasing day by day. Transportation sector is believed to be one of the highest contributor to the world’s global carbon dioxide emission at 28% in 2017 as claimed by US EPA. This is a worrying issue as more cars are being used by every people to commute every day, this will increase the emission. Therefore, alternatives and solutions should be implemented to tackle this environmental issue and one of the solutions is using alternative powertrain such as hybrid and electric vehicles. In this paper, the carbon footprint will be studied for three powertrains including the two mentioned before and internal combustion engine, from a case study of Volvo XC40 that has all these variants. Prior work had studied experimentally the effect of the powertrains to the environment, but the comparison is not clear between those three. In this paper, an apple to apple comparison was made as all the three vehicles are made from the same manufacturer, is ideal and latest in 2021, and has minimum other differences between them. The method used is life-cycle-analysis (LCA) for each vehicles to determine carbon footprint in each life cycle to make the comparison fair and square. Then, a projection of the carbon footprint are made until 2040. The key results are; ICEV produce the highest emission, followed by BEV and PHEV with 8558, 5818 and 5056 kgCO2/year respectively. From each scenario made for projections; total CO2 emissions in Scenario 2 (30% BEV) is 1.5353x10^12 kgCO2, lowest compared to Scenario 1 (BAU) and 3 (30% ICE) that produce 1.42488 x 10^13 kgCO2 and 9.70414 x 10^13 kgCO2 respectively.